FORMULATION OF SELF-NANOEMULSIFYING DRUG DELIVERY SYSTEM OF BOVINE SERUM ALBUMIN USING HLB (HYDROPHILIC-LYPOPHILIC BALANCE) APPROACH - Winarti, Lina (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2016)
Self-Nanoemulsifying Drug Delivery System (SNEDDS) has potential to be developed for oral protein delivery because it is free from water, hence preserving the stability of protein, protecting protein from enzymatic degradation, and enhancing the protein permeability in the gastrointestinal tract (GIT). However, protein-based SNEDDS formulation is challenging due to low solubility property of protein in oil, which is towards zero. This present study aimed to obtain the most compatible SNEDDS system for protein using HLB approach. Bovine serum albumin (BSA) was used as a protein model in this study. A number of 78 formulae with HLB ranging between 11 and 15 were screened to acquire stable SNEDDS composition without the presence of phase separation. Of 13 stable formulae, two were selected (F30, F45) with HLB 15, and then loaded with BSA. Physical characteristics of both formulae were then evaluated and the results suggested that SNEDDS with single hydrophilic surfactant (F45) and HLB 15 was the best formula for protein template as the stability testing showed that phase separation and precipitation did not appear. It was robust to pH and dilution with percentage of transmittance of 96.40Â±1.05% and the droplet size of 180.9nm. F45 also had uniform distribution of droplets size since the polydispersity index was less than 0.1. The zeta potential of F45 was -0.12mv with loading efficiency 83.57Â±1.77%. The emulsifying time of F45 was > 2min due to the formation of crystalline gel that was difficult to disperse.